2021
DOI: 10.1007/s40726-021-00194-4
|View full text |Cite
|
Sign up to set email alerts
|

Health Effects of Occupational Noise

Abstract: Purpose of Review Workplace noise negatively impacts health, and noise-induced hearing loss is the most common work-related disease in many countries. Occupational noise may also cause cardiovascular disease, and there is epidemiologic evidence on the non-auditory effects of noise. This paper aims to briefly present and summarize the latest evidence on the auditory and non-auditory health effects of occupational noise exposure from the last 5 years. Recent Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 85 publications
1
14
0
1
Order By: Relevance
“…Moreover, in a review by Pretzsch et al, the interaction between noise as an acute or chronic stressor and the consecutive distribution of stress hormones such as adrenaline, noradrenaline, and cortisol has been mentioned. 31 Noise is a psychological stimulus that can be a threat for homeostasis since it activates the central nervous system structures of emotional processing. Therefore, given the stress model, people achieve stability by "allostasis".…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a review by Pretzsch et al, the interaction between noise as an acute or chronic stressor and the consecutive distribution of stress hormones such as adrenaline, noradrenaline, and cortisol has been mentioned. 31 Noise is a psychological stimulus that can be a threat for homeostasis since it activates the central nervous system structures of emotional processing. Therefore, given the stress model, people achieve stability by "allostasis".…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have reported hearing loss, cardiovascular disease, premature birth, and other medical conditions as diseases that can be caused by occupational noise exposure. [25] Based on that clinical evidence, institutional arrangements and environmental standards for working environments have been made. However, awareness of vocal fold diseases caused by noise exposure is still lacking, even though it was rst pointed out in the 1970s.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to excessive noise levels can cause many health problems such as stress [5], peripheral vascular irritation and hypertension [6,7], cardiovascular problems [8,9], fatigue, sleep disorders, psychosis, and hearing loss [10,11]. Also, excessive exposure to noise can increase oxidative stress and decrease speech comprehension, concentration, and performance in individuals and ultimately increase the risk of accidents in the workplace [12][13][14]. Therefore, the need to address the noise-related issues as well as prevention of health issues caused by such exposures can also be justified from an economic viewpoint [15].…”
Section: Introductionmentioning
confidence: 99%